Universal and parochial influences on journalistic ethics / Dr. Halimahton Shaari - Shaari, Halimahton (Dr.) (Faculty of Communication and Media Studies (FCMS), 2004)
Studies on communication ethics are riddled with complexities that are due in large part to the fact that the concept of ethics is very often viewed as subjective. This subjective nature of the ethics stem from the fact that ethical considerations and decisions are made based not just on personal moral inclination, but also a host of other factors of a socio-cultural and political nature.